Effect of 2-Propanol on surface properties and wetting behavior of surfactants on the glass surface - Sujit Kumar Shah; Pankaj Kumar Das; Ajaya Bhattarai (Heliyon)
This study investigates the effects of 2-Propanol (2-PrOH) on the surface and wetting properties of anionic - Sodium bis(2-ethyl hexyl) sulfosuccinate, also known as Aerosol AT (AOT), Sodium Dodecyl Sulfate (SDS) – and cationic – Cetylpyridinium Chloride (CPC) and Cetyltrimethylammonium Bromide (CTAB) surfactants on a glass surface. Key surface properties including surface tension(γ), critical micelle concentration (CMC), surface excess concentration (Γmax), and minimum surface area per molecule (Amin), were determined in water and varying parts by volume (0.10, 0.20, and 0.30) 2-PrOH at 298.15 K. Additionally, Contact angle (CA), Adhesion tension (AT) and Work of Adhesion (WA) were analyzed to assess the impact of 2-PrOH on the wettability of the surfactant solutions. The results show that adding 2-PrOH significantly reduces the γ and CA, enhancing the wetting properties of all surfactants. Γmax decreases, while Amin increases, indicating a more dispersed arrangement of surfactant molecules at the air/solution interface in the presence of 2-PrOH. This leads to improved spreading and adhesion on the glass surface, as demonstrated by increased AT and WA with increasing 2-PrOH parts by volume. The study concludes that 2-PrOH acts as an effective co-surfactant optimizing surfactant performance by lowering the γ and enhancing liquid/solid interactions, making these systems more effective in applications requiring strong wetting and adhesion. These findings provide valuable insights for designing surfactant formulations for industrial applications such as coatings, detergents, and surface treatments.